Global poverty how global governance is failing the poor - Hulme, David (New York Routledge, 2010)
Around 1.4 billion people presently live in extreme poverty, and yet despite this vast scale, the issue of global poverty had a relatively low international profile until the end of the 20th century. In this important new work, Hulme charts the rise of global poverty as a priority global issue, and its subsequent marginalisation as old themes edged it aside (trade policy and peace-making in regions of geo-political importance) and new issues were added (terrorism, global climate change and access to natural resources).
Includes index
Keywords: Poverty -International cooperation